The impacts from SrS:Cu+,Na and LaOF:Eu3+ phosphors on color and luminous performances at 5600 K–8000 K WLEDs - Ha Thanh Tung; Huu Phuc Dang (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In terms of lumen performance, the remote phosphor structure can yield better results than the conformal phosphor and in-cup phosphor packages. The application of such a package in LEDs might make the manipulation of the device’s chromatic performance challenging. Two remote phosphor packages are available for raising chromatic performance: one-layer and triple-layer phosphor adjustments. Using software simulation and phosphors created through specific procedures, our study was carried out to select the best adjustment that provides the best results in white LEDs (WLEDs) implemented with many chips: color rendering index (CRI), color quality scale (CQS), lumen output (LO), along with chromatic uniformity. We utilized the WLEDs at five temperatures of color between 5,600 K and 8,500 K. From the outcome, we can consider the three-layer phosphor package to have greater CRI, CQS, and lumen efficiency (LE). Notably, CQS and LE receive a roughly 30% boost compared to singular-layer package. The package can also reduce the chromatic deviation by roughly 30% to 50%, and therefore, grants a boost in chromatic homogeneity. To authenticate these outcomes, the dispersion attribute underwent examination in the layers of phosphor based on Mie-dispersion hypothesis. The outcome may prove useful for creating WLED devices with greater standards.